Revisit the history of early settlements in Pulau Pinang: the contributions and legacies of Rawa people - Abdullah, Suhaila; Fathil, Fauziah (IIUM Press, 2021)
It is common that the history of Pulau Pinang has often been affiliated with British as pioneers even among Malaysians, almost to the point of no return. This despite the fact that there had been Malay groups of both local and regional origin who had made Pulau Pinang as their homeland long before the coming of the British. Of the second group, Rawa people from West Sumatera were neither strangers to Pulau Pinang Island nor the mainland area that formed part of the northern state i.e. Seberang Perai. Adopting a content analysis approach via library research and qualitative methods, plus interviews involving the Rawa people of the state, the paper aims to highlight the often-dismissed fact that the Rawa people along some other Sumatran migrant groups had contributed to the early development of Pulau Pinang. Only recently that several studies came to prove the existence of Malay settlements on the Island prior to its so-called foundation by British explorer representing the British East India Company, Francis Light in 1786. This paper is to provide further proofs in that direction as the early Malay settlers deserved acknowledgement for the contributions made and recognition for the legacies left behind. Apart from assessing various reasons for the Rawa migration and their early areas of settlements, more importantly, the paper demonstrates that the Rawa migrants throughout their long years of existence in the state have contributed to the socio-economic and political developments of Pulau Pinang.